2004
DOI: 10.1002/macp.200300184
|View full text |Cite
|
Sign up to set email alerts
|

Triblock Copolymers Based on 1,3‐Trimethylene Carbonate and Lactide as Biodegradable Thermoplastic Elastomers

Abstract: Summary: Biodegradable triblock copolymers based on 1,3‐trimethylene carbonate (TMC) and different lactides (i.e. D,L‐lactide(DLLA), L‐lactide (LLA), D‐lactide (DLA)) designated as poly(DLLA‐TMC‐DLLA), poly(LLA‐TMC‐LLA) and poly(DLA‐TMC‐DLA) were prepared and their mechanical and thermal properties were compared with those of high molecular weight poly(TMC) and poly(TMC‐co‐DLLA) statistical copolymers. Triblock copolymers containing crystallizable LLA or DLA segments perform as thermoplastic elastomers (TPEs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
138
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 40 publications
3
138
0
2
Order By: Relevance
“…Thus, physical properties should be improved by copolymerizations of lactide with other monomers in order to generate softer and tougher materials. For this purpose, cyclic carbonates are of great interest as comonomers because of the soft property of the resulting copolymers [11][12][13][14][15][16][17]. In our previous works, we studied synthesis and biodegradabilities of random copolymers of L-LA with (R)-, (S)-, or rac -1-methyltrimethylene carbonate polymerized by using a samarium initiator (C 5 Me 5 ) 2 SmMe(THF) (Sm1) [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, physical properties should be improved by copolymerizations of lactide with other monomers in order to generate softer and tougher materials. For this purpose, cyclic carbonates are of great interest as comonomers because of the soft property of the resulting copolymers [11][12][13][14][15][16][17]. In our previous works, we studied synthesis and biodegradabilities of random copolymers of L-LA with (R)-, (S)-, or rac -1-methyltrimethylene carbonate polymerized by using a samarium initiator (C 5 Me 5 ) 2 SmMe(THF) (Sm1) [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Feijen et al [22] has reported the blends of biodegradable triblock copolymers based on 1,3-trimethylene carbonate (TMC) and different lactides (i.e. L-lactide (LLA), D-lactide (DLA).…”
Section: Compound Modificationsmentioning
confidence: 99%
“…Polymer micelles are aggregates formed from polymers containing hydrophilic and hydrophobic segments, where various functions can be imparted to the structure by the polymer design. For the hydrophobic polymer segment we have focused on PTMC, which has an amorphous structure and is an attractive material in terms of degradability in vivo [1][2]. For the hydrophilic block, PNIPAAm and PMPC are attractive, and they are broadly used in the biomedical field, where PNIPAAm shows thermo-responsive behavior and PMPC polymer shows high water solubility and high compatibility in vivo.…”
Section: Introductionmentioning
confidence: 99%